"Arming half-baked people with weapons!" Information enclaving among professionals and the need for a care-centred model for antibiotic use information in Uganda, Tanzania and Malawi - Nayiga, S.; MacPherson, E.E.; Mankhomwa, J.; Nasuwa, F.; Pongolani, R.; Kabuleta, R.; Kesby, M.; Dacombe, R.; Hilton, S.; Grace, Delia; Feasey, N.; Chandler, C.I.R. (Informa UK Limited, 2024)
Background The overuse of antimicrobial medicines is a global health concern, including as a major driver of antimicrobial resistance. In many low- and middle-income countries, a substantial proportion of antibiotics are purchased over-the-counter without a prescription. But while antibiotics are widely available, information on when and how to use them is not.